2022
DOI: 10.1007/s10456-022-09844-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic angiogenesis for patients with no-option critical limb ischemia by adipose-derived regenerative cells: TACT-ADRC multicenter trial

Abstract: Background Patients with critical limb ischemia (CLI) still have a high rate of lower limb amputation, which is associated with not only a decrease in quality of life but also poor life prognosis. Implantation of adipose-derived regenerative cells (ADRCs) has an angiogenic potential for patients with limb ischemia. Objectives We investigated safety, feasibility, and efficacy of therapeutic angiogenesis by cell transplantation (TACT) of ADRCs for those patients in multicenter clinical trial in Japan. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Our retrospective analysis of the SVF therapy trial for terminal CLI 46 supports a positive correlation between complete recovery and high numbers of injected CD271 + progenitors, while amputated/recurrence of CLI was associated with low numbers. Importantly, we determined that approximately 300,000 to 500,000 AT-CD271 + progenitors per lesion area (CD271 + cells / ulcer cm 2 ) as the dose that seems to be necessary for favorable outcome.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our retrospective analysis of the SVF therapy trial for terminal CLI 46 supports a positive correlation between complete recovery and high numbers of injected CD271 + progenitors, while amputated/recurrence of CLI was associated with low numbers. Importantly, we determined that approximately 300,000 to 500,000 AT-CD271 + progenitors per lesion area (CD271 + cells / ulcer cm 2 ) as the dose that seems to be necessary for favorable outcome.…”
Section: Discussionsupporting
confidence: 64%
“…To further investigate the therapeutic potential of CD271 + progenitors, we retrospectively evaluated data from a limited human cell therapy trial (multi-center clinical trial of SVF therapy) for no-option CLI patients 47 ( Figure 7A and 7B ). During the one-year follow-up period, patients received no interventional treatments (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This response triggers angiogenesis and collateral vessel development [ 133 , 134 ]. Therapeutic promotion of angiogenesis by delivery of VEGFA is therefore one approach in cases of acute ischemia [ 135 , 136 ]. Multiple strategies using growth factor- or cell-based therapies to promote blood vessel development have been described with different levels of success [ 137 , 138 ].…”
Section: Angiogenesis and Anti-angiogenesis In Diseasesmentioning
confidence: 99%
“…Recently, the development of novel therapeutic angiogenesis cell sources, such as adipose-derived regenerative cells (ADRCs), has been investigated in no-option CLTI patients [ 22 ]. The results of this multicenter clinical trial demonstrated the safety, feasibility, and effectiveness of autologous ADRCs implantation for therapeutic angiogenesis, resulting in high major amputation-free survival rates (94.1%) at 6 months in no-option CLTI patients.…”
Section: Discussionmentioning
confidence: 99%